(untitled) (Muitas Vozes, 2021)
The literary production delivered to the children are an ideal context to produce social representations to child audience identify themselves. For this reason, it is an opportunity to question where the place to the diversity of the identitary representations, in special the ones from people with disability, that claim, legitimately, for more visibility in the field of artistic-cultural productions is. Based on this assumption, the objective of this article is to investigate one number of a Brazilian comic book called Monica‘s Gang, by Mauricio de Sousa, in order to analyze the approach that the narrative gives to the child with Autistic Spectrum Disorder. Originally published in 2002 and with guaranteed distribution up to the present day, the aforementioned issue is entitled Monica´s Gang - a different litlle friend and highlights the character of an autistic boy called André. When examining the constitution of this character, we found that the autist child projection is still lined with stigmas, which are translated by his limited place of speech in the narrative. The theoretical contribution came up from the studies about representation promoted by Hall (2016); studies about Autism carried out by Gaiato and Teixeira (2018); also contemplating the peculiarities of comic narratives in the perspective of McCloud (1995).